Program One Day One Juz: Strategi Budaya Mencintai Al-Qur'an di Lembaga Pendidikan Boarding School - Hakim, Muhammad Nur; Sirojuddin, Akhmad; Apriliyanti, Sylvia Budi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This research aims to examine the effectiveness of implementing Islamic educational culture through the One Day One Juz (ODOJ) program at Ar-rohmah Boarding School Malang in increasing students' love for the Al-Qur'an. The method used is qualitative with a case study approach, collecting data through observation, interviews, and documentation. The results of the research show that the ODOJ program has succeeded in strengthening students' relationship with the Al-Qur'an, which is marked by an increase in the quality of reading the Al-Qur'an according to tajwid, increased reading speed, frequency of reciting the Al-Qur'an, and the desire to memorize Al-Qur'an. Koran. Apart from that, there are positive changes in the morals of the students, such as increasing politeness, honesty, responsibility, cooperation, and activeness in congregational prayers as well as academic and non-academic achievements. This research concludes that the application of Islamic educational culture through the ODOJ program at Ar-rohmah Boarding School has succeeded in creating a 'Walking Al-Qur'an' among students, where the values ​​of the Al-Qur'an are internalized in daily behavior. This research contributes to the development of cultural management of Islamic education, especially in designing and implementing programs that support the achievement of the vision, mission, and goals of Islamic education.